A Case Report on Costochondritis: Clinical Insights and Management Strategies - Thomas, Angelin Grace; Suresh, Aswini; Singam, Ann Jency Arul Durai (Indian Journal of Pharmacy Practice)
Costochondritis is a self-limiting inflammatory condition affecting the costochondral and chondrosternal joints, often presenting with localised chest pain. This case report discusses a 50-year-old male with a history of type II diabetes who presented with chest pain, cough, weight loss, and generalised fatigue. The clinical assessment, including physical examination, laboratory tests, and imaging, led to a diagnosis of costochondritis. The patient's symptoms were distinguished from other serious conditions like myocardial infarction and pneumonia through tenderness on palpation of the costosternal joints, a normal chest X-ray, and ECG findings. Laboratory results showed mild inflammation, liver and renal function abnormalities, likely due to medication use. Treatment focused on pain relief, anti-inflammatory therapy, and symptom management, including antibiotics, analgesics, and muscle relaxants. The patient’s condition improved, and he was discharged with a comprehensive medication regimen. This case highlights the importance of considering costochondritis in the differential diagnosis of chest pain and emphasises the need for a tailored treatment approach, as well as regular follow-up to prevent complications.
Keywords: Costochondral joints; Inflammatory conditions; Chest pain